2008
DOI: 10.1002/macp.200800027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fullerene on Photocurrent Performance of 6‐O‐Porphyrin‐2,3‐di‐O‐stearoylcellulose Langmuir‐Blodgett Films

Abstract: Thin films consisting of 6‐O‐porphyrin‐2,3‐di‐O‐stearoylcellulose (H2PCS) and fullerene (C60) were fabricated for anodic photocurrent generation systems by the Langmuir‐Blodgett (LB) technique. The π‐complexation between the porphyrin moiety and C60 in the LB films was investigated by means of the surface pressure (π)‐area (A) isotherms, UV‐vis, and fluorescence spectroscopy. The photocurrent density generated from the H2PCS–C60 LB monolayer films exhibited an increase with increasing the C60 proportion and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…This assembly is interesting because the scaffold can be immobilized onto gold surface through a thio-terminated linker to create a functionalized electrode for photoelectrochemical applications. In another report, porphyrins have been attached to a cellulose motif designed to encapsulate C 60 , and the films of this material fabricated by a LB technique exhibited photo-currents 289. Mixtures of C 60 with simple tetraphenylporphyrins, and those appended with long alkyl chains, cast on ITO surfaces do not form films and often separate into the two components because the π-π interactions are insufficient to maintain an organized structure.…”
Section: Porphyrins and Fullerenes Architecturementioning
confidence: 99%
“…This assembly is interesting because the scaffold can be immobilized onto gold surface through a thio-terminated linker to create a functionalized electrode for photoelectrochemical applications. In another report, porphyrins have been attached to a cellulose motif designed to encapsulate C 60 , and the films of this material fabricated by a LB technique exhibited photo-currents 289. Mixtures of C 60 with simple tetraphenylporphyrins, and those appended with long alkyl chains, cast on ITO surfaces do not form films and often separate into the two components because the π-π interactions are insufficient to maintain an organized structure.…”
Section: Porphyrins and Fullerenes Architecturementioning
confidence: 99%
“…The chromophores are spaced at a fixed distance using cellulose with its rigid structure and thus the photocurrent quantum yields for the LB films are increased (Sakakibara & Nakatsubo, 2008b). A further improvement of photocurrent performance was obtained by the incorporation of fullerene (C60) in porphyrin-cellulose films (Sakakibara & Nakatsubo, 2008a).…”
Section: Fluorescence Of Polysaccharides and Polysaccharide Derivativesmentioning
confidence: 99%
“…ZnPCS [7] : To a solution of H 2 PCS (9.0 mg, 5.9 mmol based on porphyrin moiety) in CH 2 Cl 2 (2 mL), zinc(II) acetate (20 mg, excess) in MeOH (1 mL) was added. The reaction mixture was stirred under light shielding overnight and then treated with the same work-up procedure as MgPCS to give ZnPCS (6.0 mg, 64%).…”
Section: Metalation Of Porphyrin Groupsmentioning
confidence: 99%
“…The uniform and well‐defined structure affords precise control of the positioning of porphyrins attached to cellulose scaffold, mimicking the array of natural photosynthetic light‐harvesting systems. In addition, we have recently reported the fabrication of mixed LB films of H 2 PCS and fullerene C 60 and found that the photocurrent quantum yield was rather improved because of the complexation of C 60 with the porphyrin moieties attached to rigid cellulose scaffold 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation